Pengaruh Love Of Money Terhadap Pola Perilaku Konsumsi Islami Dengan Locus Of Control Sebagai Variabel Moderating - Ni’ma Ainun (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2024)
Abstract: This study aims to analyze the effect of Love of Money on Islamic Consumption Behavior Patterns with Locus of Control as a moderating variable, focusing on the community in Waetuo Village. This research employs a quantitative approach and involves 98 respondents selected using the Purposive Sampling technique. Data were collected through questionnaires and analyzed using SPSS version 25.The results of the study indicate that: (1) Love of Money does not have a significant influence on Islamic Consumption Behavior Patterns, with a significance value of 0.104, which is greater than 0.05. (2) Based on analysis using Moderated Regression Analysis (MRA), it is shown that Locus of Control can function as a moderating variable that strengthens the negative effect of Love of Money on Islamic Consumption Behavior Patterns. However, this result does not require further discussion because the moderation depends on the validity of the first hypothesis.